Pendugaan Fungsi Intensitas Proses Poisson Periodik dengan Tren Fungsi Pangkat Menggunakan Metode Tipe Kernel - Rachmawati, Ro’fah Nur (Bina Nusantara University, 2011)
Stochastic process has an important role in many areas in everyday life, including the customer service process. The number of customers who come to a service center will be different for each particular time. A special form of stochastic process with continuous time and discrete state space is periodic Poisson process, which is a Poisson process with an intensity function of a periodic function. However, on the stochastic modeling of a phenomenon by a periodic Poisson process, the intensity function of the process is generally unknown. Therefore, a method is needed to infer the function. In this article, a Kernel estimator is formulated from a periodic Poisson process with a trend component in a rank function, which is divided into two cases; the identified rank function coefficient and the unidentified rank function coefficient.